Financial Sustainability Ratio And Aspects That Affect It - Andi Rustam; Muhammad Adil (Jurnal Akuntansi, 2022)
This study aims to examine the effect of Return On Assets (ROA), Capital Adequacy Ratio (CAR), Company Size, Operating Expenses Operating Income (OEOI), Loan To Deposit Ratio (LDR) affect the Financial Sustainability Ratio. The population in this study is the financial report data of Islamic Commercial Banks on Islamic banking statistics from January 2018 to December 2020. Sampling was done by purposive sampling method with the criteria; Islamic Commercial Banks are not in a problematic condition, or the BUS can generate profits in carrying out its operations and has been published in the Financial Services Authority (OJK). Secondary data was collected through the Indonesia Stock Exchange website and analyzed using Multiple Regression Analysis with the Ordinary Least Square model using the Eviews Version 12 software. The results found that ROA had no significant effect on the Financial Sustainability Ratio. CAR, Company Size, and LDR have a positive and significant impact on the Financial Sustainability Ratio. In contrast, OEOI was found to have a negative and significant effect on the Financial Sustainability Ratio.